Blockchain based Secured Multipurpose Identity (SMID) management system for smart cities - Rahat, Abrarul Hassan; Joti, Tassnim Jaman; Akter, Tania; Tasnin, Humayra; Rumon, Mamunur Rashid (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.